Dietary Enterococcus faecium NCIMB 11181 supplementation mitigates intestinal and systemic inflammation induced by avian pathogenic Escherichia coli O78 infection in broiler chickens - Pengfei Li; Yuanyuan Wu; Ruichen Bi; Changchang Cao; Jinming Hu; Xiaoxue Chen; Tong Luo; Zhong Wang (Poultry Science)
The development of non-antibiotic agents to control avian colibacillosis has become urgent work. Probiotics Enterococcus faecium strains are promising antibiotic alternatives to combat pathogen infection. This study investigated the protective efficacy and action mechanism of dietary probiotic Enterococcus faecium NCIMB 11181 (E. faecium 11181) supplementation on broilers infected with avian pathogenic Escherichia coli (APEC) O78 by measuring immune functions and intestinal microbiota. A total of 120 one-day-old male Arbor Acres broiler chicks were randomly assigned to a 2 × 2 factorial arrangement of treatments with two dietary E. faecium 11181 levels (0 or 2 × 108 CFU/kg of diet) and two disease challenge status (control or APEC O78 challenged). APEC infection model was induced via intra-tracheal inoculation of APEC O78 at 19 d of age. The results indicated that dietary E. faecium 11181 addition mitigated local and systemic inflammation caused by APEC O78 infection through decreasing spleen organ index and Escherichia coli (E. coli) counts (P < 0.05), intestinal cell apoptosis index (0.05 < P < 0.1); downregulating splenic NF-κB and IL-17 mRNA abundances as well as peripheral blood B lymphocytes proliferation activity (P < 0.05); upregulating the genes expression levels of antimicrobial peptides (β-defensin-1, -2, -4, -6 and -7), A20, Tollip, TGF-β2 and TGF-β3 genes in the spleen (P < 0.05); and increasing peripheral blood CD4+ T lymphocytes numbers (P < 0.05). Furthermore, E. faecium also improved intestinal microbial composition of the infected birds by enriching Alistipes, Faecalibacterium, and Lactobacillus, and reducing Helicobacter, Coprobacter, and Escherichia Shigella in the cecum of the infected chickens (P < 0.05). Collectively, our results suggested that dietary E. faecium 11181 addition could alleviate local and systemic inflammation induced by APEC O78 infection through inhibiting the over-activation of TLR-NF-κB signal pathway, inducing the expression of endogenous antimicrobial peptides, enhancing peripheral blood CD4+ T lymphocytes functions and improving gut microbiome.